Angioscintigraphic Assessment of Arterial and Portal Liver Blood Flow: Comparison with Splanchnic Angiography - Zatta, G.; Santambrogio, R.; Boccolari, S.; Mana, O.; Gattoni, F.; Baldini, U.; Galeotti, F.; Opocher, E.; Spina, G. P.; Tarolo, G. L. (Nuklearmedizin - NuclearMedicine, 1987)
In order to validate an angioscintigraphic method for the evaluation of the components of hepatic blood flow, the results of angioscintigraphy were compared with splanchnic angiography in 25 cirrhotics. Two indices of hepatic portal perfusion and a splenohepatic arterial index were calculated. These were correlated with portal diameter and hepatic artery diameter, respectively. No correlation was found between grades of portal perfusion according Nordlinger’s criteria and these indices. The method is very simple and could be applied to evaluate the changes of liver hemodynamics induced by drugs or shunt surgery.